2008
DOI: 10.4161/cc.7.24.7379
|View full text |Cite
|
Sign up to set email alerts
|

E2F2 represses cell cycle regulators to maintain quiescence

Abstract: E2F transcription factors control diverse biological processes through regulation of target gene expression. However, the mechanism by which this regulation is established, and the relative contribution of each E2F member are still poorly defined. We have investigated the role of E2F2 in regulating cellular proliferation. We show that E2F2 is required for the normal G 0 /G 1 phase because targeted disruption of the E2F2 gene causes T cells to enter S phase early and to undergo accelerated cell division. A larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 57 publications
5
88
1
Order By: Relevance
“…The accelerated initial proliferation Loss of E2F1 and E2F2 leads to DDR and senescence A Iglesias-Ara et al of E2F1/E2F2 À/À BMDM indicates that normally E2F1 and E2F2 function to suppress proliferation of this cell type. The increased expression in E2F1/E2F2 À/À BMDM of E2F target genes that function in DNA replication and cell cycle progression is the apparent cause of accelerated DNA replication, similar to previous findings in T lymphocytes (Infante et al, 2008). Furthermore, our results imply that the repressor role of E2F1/E2F2 may not be limited to post-mitotic differentiating cells, a function that has been recently shown for E2F1-3 (Chen et al, 2009; Chong et al,…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The accelerated initial proliferation Loss of E2F1 and E2F2 leads to DDR and senescence A Iglesias-Ara et al of E2F1/E2F2 À/À BMDM indicates that normally E2F1 and E2F2 function to suppress proliferation of this cell type. The increased expression in E2F1/E2F2 À/À BMDM of E2F target genes that function in DNA replication and cell cycle progression is the apparent cause of accelerated DNA replication, similar to previous findings in T lymphocytes (Infante et al, 2008). Furthermore, our results imply that the repressor role of E2F1/E2F2 may not be limited to post-mitotic differentiating cells, a function that has been recently shown for E2F1-3 (Chen et al, 2009; Chong et al,…”
Section: Discussionsupporting
confidence: 91%
“…These results argue for a positive role for E2F1-3 in cell cycle progression. By contrast, we and others have shown that loss of E2F2, or more dramatically, the combined loss of E2F1 and E2F2 impairs cellular quiescence and leads to accelerated replication of DNA of several cell types, implying a negative role for these proteins in proliferation control (Murga et al, 2001;Zhu et al, 2001;Infante et al, 2008;Pusapati et al, 2010). Moreover, loss of E2F leads to deficient erythropoiesis, which has been associated with increased DNA double-stranded breaks and cell cycle arrest (Dirlam et al, 2007), although the source of the DNA damage has not been identified.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…They have been reported to promote cellcycle entry and progression upon their ectopic expression. 16 By contrast, targeted inactivation of these E2Fs revealed their essential role in sustaining quiescence in hematopoietic cells, 11 in supporting survival of progenitor cells 16 or in facilitating exit from the cell cycle in differentiating cells. 13,17 However, the mechanisms by which E2F1 and E2F2 accomplish such diverse functions remain unresolved.…”
mentioning
confidence: 98%
“…[8][9][10] E2F1 and E2F2 are known to function both as transcriptional activators and as repressors of their target genes, including those coding for microRNAs. [11][12][13][14][15] Moreover, E2F1 and E2F2 perform positive as well as negative regulatory roles in cellular proliferation, which appear to be cell specific and context dependent. They have been reported to promote cellcycle entry and progression upon their ectopic expression.…”
mentioning
confidence: 99%